Association of alpha-1 acid glycoprotein with hepatic steatosis and liver fibrosis among women: a population-based study - Sichang Wang (BMC Gastroenterology)
Abstract Background and aim The alpha-1-acid glycoprotein (AGP) is a novel inflammatory biomarker, and inflammation has been implicated in hepatic steatosis and fibrosis. The objective of this study was to investigate the relationship between AGP and hepatic steatosis and hepatic fibrosis and to assess its value as a potential biomarker. Methods and results In this study, the authors used data from NHANES between 2017 and 2023, adopting a cross-sectional design. In the multivariate linear regression model, the natural logarithm of alpha-1-acid glycoprotein (Ln AGP) was considered in relation to CAP and LSM. Smooth curve fitting was performed to address potential nonlinear relationships. The study involved 2,608 adult women aged 18 to 49 years. Multivariate linear regression analysis indicated a significant positive association between Ln AGP and CAP (β = 17.80, 95% CI: 10.56–25.05; P < 0.0001), suggesting that higher AGP levels may be correlated with greater hepatic steatosis. However, no statistically significant linear association was found between Ln AGP and LSM (β = -0.40, 95% CI: -0.93 to 0.12; P = 0.1307). Importantly, subsequent analysis revealed a significant L-shaped nonlinear association, with an inflection point identified at an Ln AGP of 0.05 g/L. It is important to note that due to the cross-sectional design, these findings reflect associations rather than causal relationships. Conclusions Our cross-sectional study found that elevated AGP concentrations are associated with greater hepatic steatosis (CAP; β = 17.80, 95% CI: 10.56–25.05; P < 0.0001), though this design cannot establish causality. For hepatic fibrosis (LSM), while no significant linear association was observed (β = -0.40, 95% CI: -0.93 to 0.12; P = 0.1307), a significant nonlinear L-shaped relationship was identified, indicating a complex association. These findings highlight the necessity for future research to investigate potential causal relationships between AGP and liver health.